Fiscal and monetary policy in an SFC model of the Italian economy - Francesco Zezza (Levy Economics Institute of Bard College, 2024)
Following the Great Financial Crisis of 2008-9, there has been a shift in mainstream economic policy modeling toward "realism," with dynamic stochastic general equilibrium (DSGE) models partly diverging from the representative agent framework, and large-scale, New-Keynesian structural models addressing real-financial interactions in greater detail. Still, the need for tractability of the former, and the lack of theoretical structure of the latter prevented the complete introduction of a modern-and complex-multi-sector/multi-asset financial system in policy models in use at central banks and treasuries. However, empirical models adopting the StockFlow Consistent (SFC) approach resolved most of these complications with a surge in the number of country models over the last few years. The present work lays out the main out-of-sample features of a quarterly SFC model of the Italian economy (MITA). Section 2 reviews the existing SEM models of the Italian economy, and places SFC models along the suite of policy models in use around the world, discussing the main pros and cons of adopting the SFC approach over others. Section 3 briefly presents the model structure and main behavioral equations, and discusses the main differences between and similarities with the other large scale SFC model of the Italian economy. Section 4 shows the out-of-sample properties of the model, implementing different monetary and fiscal policy shocks, and assessing their effects in terms of growth, distributional dynamics, and sectoral debt sustainability. Section 5 concludes.
Keywords: C54; E12; E17; E44; E58; 330; Empirical Stock-Flow Consistent Models; Monetary Policy; Fiscal Policy; Italy